A conceptual ITIL management framework- Non-IT functions in software industry - Rani, Preethi; Annadurai, C. (Gyan Management Journal, 2012)
Global competition which has now become fierce because of advancements in technology and changing equations in global economy has made its impact on the software industry. Service Management Framework SMF) is an offspring of Information Technology Infrastructure Library (/Tll) targeted for service functions in software companies to drive the service efficiency and effectiveness. Software companies adopt /Tll framework to streamline IT processes and practices. This article provides a framework for support functions to understand, assess, streamline, and integrate support functions operation in software companies. The framework proposed is derived from extensive survey of ITIL literature for support functions to have a one stop solution for all the employee queries and to have a value add for services provided by support functions in software companies and also track performance of function, evaluate the set targets, detailed root cause analysis for issues and continuously driving process improvements.